2020
DOI: 10.1097/md.0000000000023238
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness and safety of acupuncture for scoliosis

Abstract: Background: Scoliosis is a disease that affects all age groups and alters the three-dimensional deviation of the spinal axis. It is diagnosed when Cobb angle presents over 10 degrees and the reasons include aging, traumatic injuries, unknown origin, and disorders of congenital, neurological, musculoskeletal, and connective tissue. Scoliosis treatments are divided into surgical and conservative options. Surgery can correct the curved spine but has associated risks and economic burden. Conservative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…[36][37][38] However, there are concerns about the lack of high-quality studies examining acupuncture's effectiveness on scoliosis. 39,40 Although cupping therapy is effective in reducing overall low back pain, 38,41,42 high-quality studies on cupping therapy for scoliosis are scarce. Multiple studies have confirmed Chuna therapy or combining Chuna therapy with a different therapy is effective in reducing Cobb angle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[36][37][38] However, there are concerns about the lack of high-quality studies examining acupuncture's effectiveness on scoliosis. 39,40 Although cupping therapy is effective in reducing overall low back pain, 38,41,42 high-quality studies on cupping therapy for scoliosis are scarce. Multiple studies have confirmed Chuna therapy or combining Chuna therapy with a different therapy is effective in reducing Cobb angle.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding KM, some studies have reported acupuncture therapy is significantly effective on scoliosis 36–38 . However, there are concerns about the lack of high-quality studies examining acupuncture's effectiveness on scoliosis 39,40 . Although cupping therapy is effective in reducing overall low back pain, 38,41,42 high-quality studies on cupping therapy for scoliosis are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the role played by exercise interventions in the treatment of scoliosis is becoming more and more important. Exercise intervention measures for AIS include yoga [ 26 , 27 ], pilates [ 28 ], sling exercise [ 29 ], PSSE [ 30 – 32 ], core strength training [ 33 – 37 ], massage [ 39 ], acupuncture [ 40 ], etc. However, there is no empirical comparative study on which of these interventions have the most significant effect.…”
Section: Introductionmentioning
confidence: 99%
“…Despite persistent efforts, the existing treatments still have limitations including surgical risks, poor compliance, and negative effects. [5] Therefore, several clinical practice guidelines (CPGs) have been published to reasonably align the treatment with new scientific evidence, provide the latest knowledge, and reflect clinical practices. Among these, the International Scientific Society on Scoliosis Orthopedic and Rehabilitation Treatment (SOSORT) published the first guidelines in 2006 [6] and the third guidelines in 2018; [7] these are the most representative in terms of their use and credibility.…”
Section: Introductionmentioning
confidence: 99%
“…[4] However, the symptoms are similar regardless of the classification and include pain, leg length discrepancy, impaired posture, gait imperfections, and psychological problems, resulting in lower health-related quality of life (QOL). [5] The treatment includes surgical and conservative methods to prevent disease progression and manage the symptoms.…”
Section: Introductionmentioning
confidence: 99%